Utilization of Quercus Robur L. (fruit cups) and Salix Alba L. (Wood Extract) asdyeing agents for silk and cotton fabrics - Geelani S.M.; Bhat S.J.A.; Qazi G.; Qasba S.; Qureshi S.; Parray A.A.; Mishra P.K.; Ara S.; Sofi A.H.; Khan P.A. (My University, 2025)
Investigation was carried out to study the dyeing potential of Quercus robur L. and Salix alba L. of which fruit cups and wood extract were used as source of natural dye and mordant. Dyeing potential of the extracted material was tested on silk and cotton fabrics. Keeping in view the negative impacts of chemical agents, extraction and application was carried out using distilled water. Natural mordant used in combination with natural dye showed satisfactory results on silk fabrics both including and excluding mordant, however poor quality of dye and mordant was recorded on cotton fabric. The naturalmordant gave silk fabrics rapid dye adsorption, enhancedcolour coordinates, K/S, AE and also showed improvement in fastness properties with regard to washing, light and rubbing of the dyed silk fabric. Cotton fabric does not showed much affinity for the natural dye and mordant. © EM International.